Effect of Cooperative Learning Model Types of Stick Talking Using Simple Props to Higher Order Thinking Skill - Halimatussa’diyah Halimatussa’diyah; Mujasam Mujasam; Sri Wahyu Widyaningsih; Irfan Yusuf (Kasuari: Physics Education Journal (KPEJ), 2018)
This study was conducted to see the effect of the talking stick type of learning model by using simple teaching aids on high-level thinking skills in light material in the SMP Yapis Manokwari. Research subjects amounted to 56 students consisting of control class (class VIIIb) totaling 28 students and experimental class (class VIIIa) totaling 28 students. This type of research is quasi-experimental design with non equivalent control group design. The results showed that the data analyzed were normally distributed and homogeneous so that the hypothesis test used independent sample t-test with a significance value = 0.05. The calculation result with sig 2 tailed is 0,000 <= 0,05 so H0 is rejected and Ha is accepted. This means that there are influences of hots on students who are taught using cooperative learning model type talking stick with those taught using conventional models. In addition, the cooperative learning model type talking stick and conventional models also have an influence on students' hots with different sizes. The difference is seen in the results of the calculation of the N-gain value shows that the N-gain test of the experimental class and the control class are 0.39 and 0.38 respectively in the medium criteria. The N-gain value of the postest hots in the experimental and control classes is also 0.40. So that the experimental class and controls increase higher order thingking skill. But the posttest value in the experimental class is better than the control class.